Clara Weekly Journal - Simpson, F. S. (Francis Stephen), approximately 1831-1869. (1864)
A Voice of Our Exiles or the Clara Weekly Journal. A weekly journal compiled during the voyage of the convict ship "Clara" from England to Western Australia in 1864. Contains literary contributions from convicts and a "weekly record" of events on board.
Manuscript reference: NLA MS 6037.
Keywords: Simpson, F. S. -- approximately 1830- -- Diaries; Clara (Ship); Transportation of convicts -- Western Australia